Redundant on-screen text, learner control and self-regulation :|effects on learning past tense in English - Cananoğlu, Bedi. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study aimed to examine the effects of the redundant on-screen text, learner control and self-regulatory skills on students’ learning simple past tense in an online tutorial that were variably used. 132 EFL learners with beginner level of English studying at the preparatory school of English and vocational school of Justice participated in this quasi-experimental study. Four treatment conditions were tested: text + control, text + no control, no text + control, no text + no control), with all the groups receiving narrated slides. Each participant was given a prior knowledge test, an academic self-regulation scale, a retention test and a transfer test. Results showed that redundant on-screen text does not have a significant effect on retention or transfer scores. However, learners with control over the learning material performed significantly lower than learners without control. Out of eight tests, only one significant difference was observed between learners with high and low self regulatory skills in the transfer test when they were given learner control without on screen text. A significant two-way interaction between the treatment condition and self-regulatory skills on the retention test scores was observed; while the treatment condition and prior knowledge were found to influence students’ transfer scores independently.
Keywords: English language -- Grammar.; Internet in education.; Individual differences.